THE ONYMS IN THE NOVEL THE TIME OF THE GOATS BY LUAN STAROVA AND THEIR EQUIVALENTS IN THE NOVEL’S TRANSLATIONS IN GERMAN AND ENGLISH (Journal of Contemporary Philology, 2021)
The analysis presented in this paper focuses on three classes of onyms: zoonyms (names of animals), anthroponyms (names of persons) and toponyms (names of places), examined through the prism of their function in a particular literary work, as well as on the approaches underlying their translation, in this case, in German and English. The analysis has been conducted on a corpus compiled from a novel written in Macedonian and two of its translations. Specifically, the subject of this research are the onyms in the Macedonian novel The Time of the Goats by Luan Starova and their equivalents in the novel’s translation in German and English: what has been analysed is their function in literature and the challenges arisingfrom their transfer into another language. The term equivalent used in this paper, here primarily referred to as an equivalent of an onym, surpasses the prototypical systemic-linguistic interpretation of the notion of equivalence (complete, partial, null equivalence), especially within a literary work, and demands a substantially more precise classification of the equivalents, thus permeating into the spheres ofthe theory of translation. Hence, the subject matter of the research in this paper is not restricted to the science of names only, but in the approach underlying their transfer within an artistic literary context as well.
Keywords: onomastics; zoonyms; anthroponyms; toponyms; transfer